2020
DOI: 10.1292/jvms.20-0339
|View full text |Cite
|
Sign up to set email alerts
|

The effects of migration on the immunity of Black-Headed Gulls (<i>Chroicocephalus ridibundus</i>: Laridae)

Abstract: In order to elucidate the relationship between migration period and immunity related to susceptibility, we conducted research on Black-headed gulls ( Chroicocephalus ridibundus ). We captured 260 gulls and collected their peripheral blood. Their leukocyte (WBC) count, percentages of heterophils (Het) and lymphocytes (Lym), heterophil and lymphocyte ratio (H/L ratio), and CD4 and CD8α expression levels (CD4 and CD8α, respectively) were quantitatively analyzed over three migration periods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The following six indices of peripheral blood were used to evaluate immunity [15]: WBC was counted (cell number per deciliter), Lym and Het were calculated as the ratio of Lym and Het per 100 leukocytes using a smear stained with light Giemsa, and the H/L ratio was calculated as a ratio of these results. The number of copies of CD4 and CD8α cells in peripheral blood was calculated using real-time PCR using primers specific to Black-headed Gulls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following six indices of peripheral blood were used to evaluate immunity [15]: WBC was counted (cell number per deciliter), Lym and Het were calculated as the ratio of Lym and Het per 100 leukocytes using a smear stained with light Giemsa, and the H/L ratio was calculated as a ratio of these results. The number of copies of CD4 and CD8α cells in peripheral blood was calculated using real-time PCR using primers specific to Black-headed Gulls.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that Black-headed Gulls ( Chroicocephalus ridibundus , Laridae; winter birds in Honshu, Japan) are contaminated with Pb, and the contamination affects the heterophil and lymphocyte proportions [15]. The purpose of the present study was to determine the minimum Pb level that affects the six cells and molecules in peripheral blood with immunity function, i.e., the total number of white blood cells (WBC; cell/μL), proportion of lymphocytes (Lym; %), proportion of heterophils (Het; %), ratio of heterophils to lymphocytes (H/L ratio), copy number of CD4 messenger RNA (CD4; number of copies/μL), and copy number of CD8α messenger RNA (CD8α; number of copies/μL) in Black-headed Gulls during the winter season.…”
Section: Introductionmentioning
confidence: 99%
“…The following six indices of peripheral blood were used to evaluate immunity in Black-headed Gulls (Ushine et al 2020b): WBC count (cell number per deciliter), total Lym per 100 leukocytes and total Het per 100 leukocytes (both determined using a blood smear), Het/Lym (H/L) ratio, and copy number of messenger RNA both CD4 and CD8α, which were calculated by performing a real-time PCR with primers specific to Black-headed Gulls (GenBank® accession numbers of: LC533369 for CD4, and LC533370 and LC533371 for CD8α).…”
Section: Evaluation Of Immunitymentioning
confidence: 99%
“…Previous research has shown that Black-headed Gulls are contaminated with Pb, which affects the percentages of heterophils and lymphocytes in the peripheral blood (Ushine et al 2020b). In addition to Pb contamination, oil spills (Newman et al 2000, Seiser et al 2000, plastic ingestion (Lavers et al 2019), methylmercury exposure (Sonne et al 2020), and seabird-specific infections (Kirkwood et al 1995) have all been reported to affect the blood chemistry of seabirds.…”
Section: Introductionmentioning
confidence: 99%